Investigation of how the teaching of climatology concepts in grade12 through multimedia is done: Cases of four schools in Johannesburg North, Gauteng Province - Sethole, Mokurubane Simon (University of the Witwatersrand, Johannesburg, 2023)
The introduction of Information and Communication Technology (ICT) within education system in the 21st Century has been a motivating and encouraging phenomenon, which has completely revolutionised the way in which teaching and learning happen within the classroom. With ICT comes the usage of multimedia that has proven its significance due to its positive impact on the teaching and learning processes. This study explores and compiles good teaching practices that Grade12 educators demonstrate when teaching the climatology concepts using multimedia. Four qualified and well-experienced Geography Educators were selected from good performing schools that has ICT infrastructure. Teacher’s lessons of about 35 to 45 minutes where they taught climatology concepts using multimedia, were observed and recorded. Qualitative data collected were analysed using thematic analysis whereby categorization and combining of the trends was applied. The findings of the study reveal that the teachers under study have similar pedagogical practices during instruction when using multimedia even though their approach and multimodalities were different. This highlights the uniqueness of each individual teacher and thus proves that there is no linear way in which multimedia teaching should happen. In addition, the findings of the study reveal that the teachers valued the importance of investing time in designing multimedia adequately. They argue that teacher’s knowledge of which multimedia to use during instruction, and how such multimedia should be used, are significant to the effectiveness of their teaching of climatology concepts in Geography. Moreover, the lesson observations revealed that multimedia was used as a centralised tool to reinforce concepts taught during the lesson - in particular, the infographic. Even though teachers used different multimodalities at different stages of their lessons, it seems that teachers used multimedia as a reference tool or point. It is evident that teaching of climatology concepts with multimedia is multifaceted and it involves detailed and systematic planning, well thought instruction through efficient design and implementation and careful interactions between the teachers, students and multimedia (didactical triangle).
A thesis submitted in fulfilment of the requirements for the degree of Master of Education, to the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Multimedia; Climatology concepts; ICT (Information & Communication Technology); UCTD; SDG-4: Quality education